The Effect of Problem Based Instruction on Students’ Learning Outcomes in Respiratory System - Siregar, Rizki Aulia; Nazliah, Rahmi (FKIP Universitas Lampung, 2022)
This study aims to determine whether or not there is an influence of the learning model using the problem based instruction (PBI) learning model on student learning outcomes on the respiratory system material for class XI at the Dar al-Ma'arif Islamic Boarding School. This research method uses a quantitative approach with a quasi-experimental type of research. The population in this study were students of class XI Islamic boarding school Dar al-Ma'arif. The samples used in this study were students of class XI A (experimental class) and class XI B (control class). The samples used in this study were 2 classes totaling 40 students. Sampling in this study was conducted using a random sampling technique. Sampling in this study was carried out using a random sampling technique. The results of the study were the results of student learning outcomes using the Problem Based Instruction (PBI) learning model in the control class, the highest score was obtained at 72 while the lowest score from the control class was 36 with the average score. an average of 56.2 and while the experimental class the highest score was obtained at 96 while the lowest value from the experimental class was 40 with an average score of 66.4. The experimental class has a higher score because the use of the Problem Based Instruction (PBI) learning method is easier to understand and easy for students to understand. Keywords: problem based instruction, learning outcomes, respiratory system. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp448-458